Kemampuan Komunikasi Pelayan Beberapa Kafe Di Pantai Jimbaran - Ni Wayan Wayan Pastini; Hartanti Woro Susianti; Ariasri Nyoman Reni (Politeknik Pariwisata Makassar, 2023)
This study aims to determine the ability to communicate in English for waiters in cafes in the tourist area of Jimbaran beach. The English language is expressions of politeness in welcoming guests, in offering food and drinks, handling payments and in providing other services. The research data is in the form of primary data taken directly from English speech by waiters in interacting with foreign consumers, and collected by observation method. All data regarding grammatical errors were identified, classified, and analyzed using Lennon's theory. The method used in this research is descriptive qualitative. The results of the study indicate that there are several errors that are often found, in the form of grammatical errors in the form of addition errors and omission errors. To overcome this problem it is very important to hold training so that waiters are able to serve customers in an excellent manner. This will give a good impression to foreign consumers. So this will have a very good effect on increasing the arrival of foreign guests to Jimbaran in particular and Bali in general.